Integrative epigenome-wide analysis demonstrates that DNA methylation may mediate genetic risk in inflammatory bowel disease - N. T. Ventham (Nature Portfolio, 2016)
Epigenetic perturbations may be an important factor in diseases where both genes and environment play a role. Here, Ventham and colleagues show that DNA methylation changes in inflammatory bowel disease are related to the underlying genotype, and are associated with cell-specific changes to gene expression.